PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA PULAU PENYENGAT KOTA TANJUNGPINANG - Arie Sanyi; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Penyengat Island or known as “Pulau Penyengat Indera Sakti” is belongto world heritage conservation area which has the eminence in historical site.Furthermore, the local community who has a great potential in managing anddeveloping tourism itself. Therefore, base on RIPPDA (Rencana IndukPengembangan Daerah) of Kepri, the government of Tanjungpinang city hasassigned Penyengat Island as a main tourismspot (ODTW) in Tanjungpinangcity.Base on this case, researcher could make a research question such as inBahasa “Bagaimana Pola Pengembangan Objek Wisata Pulau Penyengat? andBagaimana Keterlibatan Masyarakat dalam Pengelolaan Objek Wisata PulauPenyengat Kota Tanjungpinang?To answer those question, researcher should follow a qualitative stepwhich consist of analyze toward developing design in RIPPDA and analyzetoward local community involvement by using community involvement scalemethod and researcher also will compare both of them.Finally, base on research result, it shows that local communityparticipation is still low. Skills, profession, open-minded and duration on stayingeffect local community involvement in managing itself. Then, the sibling issue isone of the factors that could affect that thing as well.Generally, local community is still relying the government to stimulatetheir labor in managing and developing Penyengat Island as the main Tourismin Tanjungpinang City.Key Words : Participation, managing and developing, RIPPDA